Methods for Fault Location in High Voltage Power Transmission Lines: A Comparative Analysis - Truong Ngoc Hung (International Journal of Renewable Energy Development, 2022)
Power transmission system stability can be significantly affected due to faults. The fault location accuracy in the transmission lines can make many benefits such as acceleration of the line restoration, reduction in cost, breakdown time, maintenance, and time searching. The methods based on the impedance, including the simple reactance, Takagi, modified Takagi, and double-end, are very much appreciated for locating the fault in transmission lines and especially by estimating the fault distance. This study proposes a comparative case study between these methods. The theoretical basis and the analysis, calculation, and estimation of each method are specifically re-established. To observe the performance of each method, a practical 220kV Quy Nhon - Tuy Hoa transmission line in Vietnam is used to simulate, calculate, evaluate, and compare under the various fault types and resistances. The power system is modeled and simulated in the MATLAB/Simulink software via the time domain. The voltage and current measurements at two ends of the line are used to determine the fault location on the Quy Nhon - Tuy Hoa transmission line. The simulation results show clearly the effectiveness of each fault location method.